Pengaruh Tingkat Pendidikan dan Pelatihan Terhadap Profesionalisme Guru Yayasan MAS Al-Ibrahim Bassiang Timur - Aksyai Saputra; Haedar; Saharuddin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study was conducted with the aim of knowing the influence of education and traning of the profesionalism of teachers at Madrasa Aliyah Srikandi Al-Ibrahim Bassiang Timur. The researce design uset was quantitative. The subjects of this study were all teachers at Madrasa Aliya Srikandi Al-Ibrahim Bassiang Timur, totaling 30 people. The data collection technique usetin this study was a survey with anin strument in the from of aquestionnaire. The data analysis methode uset was simple linear regression analaysis. The results of this study indicate that education and traning heve an effect on the professionalism of teachers at Madarsa Aliya Srikandi Al-Ibrahim Bassiang Timur.